2013
DOI: 10.1002/aic.14103
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide separation and dry reforming of methane for synthesis of syngas by a dual‐phase membrane reactor

Abstract: in Wiley Online Library (wileyonlinelibrary.com) High-temperature CO 2 selective membranes offer potential for use to separate flue gas and produce a warm, pure CO 2 stream as a chemical feedstock. The coupling of separation of CO 2 by a ceramic-carbonate dual-phase membrane with dry reforming of CH 4 to produce syngas is reported. CO 2 permeation and the dry reforming reaction performance of the membrane reactor were experimentally studied with a CO 2 -N 2 mixture as the feed and CH 4 as the sweep gas pass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 42 publications
0
40
0
Order By: Relevance
“…The membrane module also demonstrated good long-term stability in actual coal-derived syngas streams with 320 ppm H 2 S. The polymeric membranes cannot be used at high temperatures. The membranes with reduced thickness prepared in tubular geometry (Dong, Ortiz-Landeros, & Lin, 2013) showed improved CO 2 permeance at temperatures above 800 K. Anderson and Lin (2013) demonstrated the use of such a dual-phase membrane for hydrogen (syngas) production by dry-reforming. The membranes permeate CO 2 with O 2 , but not other gases at temperatures above 700 K. However, the membranes are not stable because stainless steel can be oxidized and also reacts with molten carbonate.…”
Section: Co 2 -Selective Membranesmentioning
confidence: 85%
“…The membrane module also demonstrated good long-term stability in actual coal-derived syngas streams with 320 ppm H 2 S. The polymeric membranes cannot be used at high temperatures. The membranes with reduced thickness prepared in tubular geometry (Dong, Ortiz-Landeros, & Lin, 2013) showed improved CO 2 permeance at temperatures above 800 K. Anderson and Lin (2013) demonstrated the use of such a dual-phase membrane for hydrogen (syngas) production by dry-reforming. The membranes permeate CO 2 with O 2 , but not other gases at temperatures above 700 K. However, the membranes are not stable because stainless steel can be oxidized and also reacts with molten carbonate.…”
Section: Co 2 -Selective Membranesmentioning
confidence: 85%
“…It was found that the carbon dioxide flux is independent by the composition and the flow rate of the sweep gas, while a certain dependency from temperature was found (Anderson & Lin, 2013). This value drops for the effect of the small leakage produced by eventual ceramic sealing at high temperature.…”
Section: Membrane Reactors For Methane Dry Reformingmentioning
confidence: 93%
“…This value drops for the effect of the small leakage produced by eventual ceramic sealing at high temperature. Using this membrane in addition to an active catalyst (Ni-g Alumina), a conversion of 88% was achieved, with an equal concentration of carbon monoxide and hydrogen in the product, and no side reactions were observed (Anderson & Lin, 2013). In particular, the CO 2 flux increases with temperature owing to the rise of ionic conductivity, and this function can be described as an Arrhenius dependency with an activation energy of 100 kJ/mol (Anderson & Lin, 2013).…”
Section: Membrane Reactors For Methane Dry Reformingmentioning
confidence: 95%
“…Reyero et al, (2013) configurations. Anderson and Lin (2013) reported that CO 2 permeation and the dry reforming reaction performance of the membrane reactor were experimentally studied with a CO 2 N 2 mixture as the feed and CH 4 as the sweep gas passing through either an empty permeation chamber or one that was packed with a solid catalyst.…”
Section: Gonzalezmentioning
confidence: 99%